2017
DOI: 10.1073/pnas.1701219114
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of colorectal cancer progression by orthotopic transplantation of engineered cancer organoids

Abstract: In the adenoma-carcinoma sequence, it is proposed that intestinal polyps evolve through a set of defined mutations toward metastatic colorectal cancer (CRC). Here, we dissect this adenoma-carcinoma sequence in vivo by using an orthotopic organoid transplantation model of human colon organoids engineered to harbor different CRC mutation combinations. We demonstrate that sequential accumulation of oncogenic mutations in Wnt, EGFR, P53, and TGF-β signaling pathways facilitates efficient tumor growth, migration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
205
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(209 citation statements)
references
References 36 publications
3
205
1
Order By: Relevance
“…However, the squamous NSCLC tumoroids (isolated from two different patients) propagated poorly under our in vitro culture conditions and underwent senescence after two (2) passages. By contrast, we were able to propagate tumoroids established from the lung adenocarcinoma (NSCLC) case for eight (8) passages. These lung adenocarcinomas tumoroid cultures were also subjected to drug screening experiments.…”
Section: Establishment Of Tumoroid Air-liquid Interface (Ali) 3d Cultmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the squamous NSCLC tumoroids (isolated from two different patients) propagated poorly under our in vitro culture conditions and underwent senescence after two (2) passages. By contrast, we were able to propagate tumoroids established from the lung adenocarcinoma (NSCLC) case for eight (8) passages. These lung adenocarcinomas tumoroid cultures were also subjected to drug screening experiments.…”
Section: Establishment Of Tumoroid Air-liquid Interface (Ali) 3d Cultmentioning
confidence: 97%
“…Interestingly, tumoroid cultures also maintain the tumor heterogeneity of the tumor-of-origin and since normal surrounding tissues can be established in addition with little modification to the culture media, a patient disease-specific genomic or proteomic tumor profile can be established in relation to the normal tissue from which the tumor arose [5,7]. Tumoroid cultures can also be implanted orthotopically in immunodeficient mice to address the impact of diseasespecific driver genes and their impact on the tumoroid's capacity to metastasize to distant organs [8].…”
Section: Priority Research Papermentioning
confidence: 99%
“…For example, tracking of photoswitched mammary tumour cells showed that, compared with primary tumour cells distant from blood vessels, cells in close proximity to blood vessels migrate extensively within and outside of the primary tumour, and later on, are also detectable at secondary sites (Kedrin et al, 2008). Similarly, genetically engineered murine and patient-derived colon organoids that express known mutational drivers of colorectal cancer progression and metastasis were longitudinally tracked following photoswitching to define the cumulative mutational load required for tumour cell migration and subsequent metastasis (Fumagalli et al, 2017). This study demonstrated that a combined mutational load affecting several signalling pathways allows colorectal cancer ; LSL-tdTomato mice; here, low-level recombination of the tdTomato allele was used to label individual crypts with tdTomato (tdTomato, red; EGFP, green; scale bar: 20 μm).…”
Section: Box 1 Subcellular Imaging Techniquesmentioning
confidence: 99%
“…[5,[14][15][16][17][18][19][20][21][22] Intestinal organoids have been used to model epithelial barrier function, interactions with microbes, infectious diseases and cancer. [23][24][25][26][27][28][29][30][31][32] Intestinal organoids derived from human samples were first grown from isolated small intestinal or colonic crypts, which are localized at the base of the intestinal and colonic epithelium, respectively. In the crypt, an adult stem cell population can be found with the capacity to replenish all intestinal epithelial cells, including absorptive and secretory cells (goblet cells, enterocytes/colonocyte, enteroendocrine cells and Paneth cells in the small intestine).…”
Section: Intestinal Organoidsmentioning
confidence: 99%
“…In addition to healthy crypts, patient tissue with specific mutations and cancer tissue has been used to derive organoid models in order to conduct drug screens. [14,[27][28][29][30][34][35][36] Both the healthy and diseased organoids were maintained in Matrigel, [14][15][16]33] yet was also shown that intestinal organoids derived from primary crypts can be maintained in ECM protein, Collagen I. [17] Matrigel is the most common ECM scaffold used for the culture and transplantation of organoids including intestinal organoids (Table I).…”
Section: Intestinal Organoidsmentioning
confidence: 99%